Original articleLow prevalence of most frequent pathogenic variants of six PARK genes in sporadic Parkinson’s disease - García, Silvia; López-Hernández, Luz; Suarez-Cuenca, Juan Antonio; Solano-Rojas, Marlene; Gallegos-Arreola, Martha P.; Gama-Moreno, Olga; Valdez-Anguiano, Paulina; Canto, Patricia; Dávila-Maldonado, Luis; Cuevas-García, Carlos F.; Coral-Vázquez, Ramón Mauricio (Folia Neuropathologica, 2014)
Genetic variants that confer susceptibility to Parkinson’s disease (PD) show unbalanced distribution among different populations; genetic predisposition to either familial or sporadic forms of PD in Mexican-mestizo population has not been comprehensively studied. The aim of the present study was to analyze genetic variants in six PARK genes in PD patients. In total 381 individuals (173 patients, 208 controls) were genotyped for p.Gly2019Ser and p.Gly2385Arg variants of LRRK2. The p.Gly2019Ser variant was present in two patients and one healthy control; the p.Gly2385Arg variant was not found. In a subgroup of early-onset PD (EOPD), MLPA analysis was done for PARKIN (PARK2), PINK1 (PARK6), DJ-1 (PARK7), LRRK2 (PARK8), SNCA (PARK1/4) and ATP13A2 (PARK9). We found a heterozygous deletion of exon 2 in PARK2 in the youngest patient of the early-onset group, who showed limited response to antiparkinsonian therapy. Although the changes Gly2019Ser and Gly2385Arg of LRRK2 are associated with PD in different populations; they may be a rare cause of PD in our population. Novel population-specific variants may underlie PD susceptibility in Mexican mestizos. Our study suggests that the heterozygous deletion of exon 2 in the PARK2 gene is a risk factor for EOPD.